Development of a numerical model of CECO wave energy converter using computational fluid dynamics - William Finnegan (2021)
As the world strives to remove its reliance on fossil fuels, wave energy presents a reliable source of renewable energy with a very high potential. Numerical simulations offer an inexpensive alternative, in comparison to physical modelling, for the development of wave energy converters. In this paper, a computational fluid dynamics model of the CECO wave energy converter (WEC) has been developed using the commercial software ANSYS CFX. In order to reduce on the computational resources required, a 2-dimensional model of this sloped (combination of heave and surge) motion WEC has been developed and then successfully validated with experimental results from physical model tests, demonstrating the capability of such models to accurately describe the response of WECs. The validated numerical model was then used to investigate the non-linear effects on the motions of CECO and to obtain more insights in relation to wave loading during a wave cycle and the viscous effects associated to the dissipation of energy in the flow around its floaters. The water particle velocity and vorticity around CECO and the heave and surge loadings on CECO, while it is in operation, are analysed and discussed. The numerical model, not only aid in the development of a new and enhanced geometry for CECO but, also, it can be used to model and analyse similar WECs. (c) 2020 The Authors